Effectiveness of Providing Social Assistance Family Hope in Improving The Economic Welfare of The Sumbul Village Community - Batubara, Yemima; Ndona, Yakobus (Ilmu Inovasi Nusantara, 2025)
Community welfare is a measure of development for a country, especially in the economic field. The Family Hope Program (PKH) is a program launched by the government in seeking community welfare. This study aims to determine the extent to which the effectiveness of the provision of family hope social assistance in improving the economic welfare of the people of Sumbul Village, Lae Parira District, Dairi Regency. This research is a type of field research with qualitative methods. Data collection techniques were carried out by observation, interview, and documentation. The types of data used are primary data obtained through interviews and documentation and secondary data obtained through journals, books, articles relevant to the topic under study. The sample selected in this study used purposive sampling technique. The data analysis technique consists of three stages starting with data reduction, data presentation, conclusion drawing and verification. The results show that 34% of beneficiary families have utilized the assistance for basic needs, but some have started to allocate it to economic sectors such as agriculture, livestock, and small businesses. The assistance is considered to have a positive impact on household economic stability, although it has not been evenly distributed to all KPM. There are also obstacles in the accuracy of targeting and the sustainability of productive utilization of assistance. In general, PKH plays an important role in supporting the economy of poor families and opening opportunities towards economic independence, but continuous evaluation is still needed so that this program can be more optimal as an instrument of poverty reduction